Chapter L'Antichità di Tadeusz Zieliński - LAROCCA, Giuseppina (Biblioteca di Studi Slavistici, 2019)
This article examines the work of Tadeusz Zieliński, philologist and scholar of Greek and Latin cultures, specifically his research devoted to Attic tragedy, to the stylistic features of Cicero, and to classical religion. Our primary focus is the evolution of Zieliński's idea of Antiquity and its relationship with Modernity, to which end we also explore the significance of the so-called "Third Slavonic Renaissance".